Software defined networking: a crucial approach for cloud computing adoption. (31st March 2022) - Badotra, Sumit; Panda, Surya Narayan
The most important convince which is contributed by the cloud is that it lets to deliver an infrastructure framework and various services rapidly instead of ordering, installing and then configuring a lot of servers, you can go for a particular number of virtual machines (VMs). Networking approach used in the cloud the network is becoming a hurdle to expand its scalability. But with the help of introducing software defined networking (SDN) approach into the cloud networking, infrastructure and its services can be configured through a well-defined application programming interface (API), manageability of the cloud network is enhanced with the capability of increasing its scalability, and therefore, the collaboration of cloud and SDN is one of the hottest topics nowadays. This study aims to provide the importance of SDN in the cloud; detailed study on its importance, architectural and advantages are stated.